CYTOKINES IN THE DIAGNOSIS OF THE SEVERITY OF THE ACTIVE PHASE OF CHRONIC PYELONEPHRITIS - D. G. Korenkov; A. L. Pavlov (Вестник урологии)
Introduction. cytokines may serve as markers of the inflammatory process during exacerbation (i.w. active phase) and further progression of chronic pyelonephritis. The estimation of cytokine constellation in this field is important problem of clinical nephrology. Purpose of the study. the aim of the study was to evaluate the severity of chronic pyelonephritis during its exacerbation by measurement of cytokines concentration in urinalysis. Materials and methods. In 64 patients with active phase of chronic pyelonephritis at the age of 25 to 65 years, the results of the study of the content of proinflammatory (iL-1β, iL-6, iL-8, TNFα, iFNγ) and anti-inflammatory (iL-2, iL-4, iL- 10) cytokines in urine taken from the ureter, bladder and blood plasma to determine the severity of exacerbation of chronic pyelonephritis. Results. The level of proinflammatory cytokine iL-8 in urine from the ureter of the affected kidney can serve as the main marker determining the severity of the active phase of chronic pyelonephritis. With a mild degree of exacerbation of the inflammatory process, the content of iL-8 in urine from the ureter is 4 times higher than normal values; at an average degree - in 8 times, and at a serious current of an exacerbation of a chronic pyelonephritis - in 54 times. Conclusions. Determination of proinflammatory cytokines in the diagnosis of the severity of pyelonephritis flow has a large diagnostic and differential diagnostic significance that will allow for differentiated therapy depending on the severity of the inflammatory process and improve the results of treatment.